Food Preservation - Advisory Board (CRC PRESS, 2007)
Food preservation involves the action taken to maintain foods with the desired properties or nature for as long as possible. The process is now moving from an art to a highly interdisciplinary science. This chapter provides an overview of food preservation methods with emphasis on inactivation, inhibition, and methods of avoiding recontamination. The final section is a discussion of the factors that need to be considered to satisfy present and future demands of the consumers and law-enforcing authorities. In most countries, innovation, sustainability, and safety have become the main foci of modern industry and economy. The United Nations World Commission on Environment and Development defined sustainable development as â€œmeeting the needs of the present generation without compromising the ability of future generations to meet their own needs.â€ A sustainable way of designing and developing food products stands to appeal to consumers, and provides a point of differentiation from competitors and a perfect platform for a range of positive public relations activities [6]. Innovation is vital to maintain progress in technology and engineering. Food safety is now the first priority of the food production and preservation industry, incorporating innovation and sustainability. The industry can compromise with some quantities such as color to some extent, but not with safety.